Rapid whole genome sequencing methods for RNA viruses - Misu, Masayasu; Yoshikawa, Tomoki; Sugimoto, Satoko; Takamatsu, Yuki; Kurosu, Takeshi; Ouji, Yukiteru; Yoshikawa, Masahide; Shimojima, Masayuki; Ebihara, Hideki; Saijo, Masayuki (Frontiers in Microbiology, 2023)
RNA viruses are the etiological agents of many infectious diseases. Since RNA viruses are error-prone during genome replication, rapid, accurate and economical whole RNA viral genome sequence determination is highly demanded. Next-generation sequencing (NGS) techniques perform whole viral genome sequencing due to their high-throughput sequencing capacity. However, the NGS techniques involve a significant burden for sample preparation. Since to generate complete viral genome coverage, genomic nucleic acid enrichment is required by reverse transcription PCR using virus-specific primers or by viral particle concentration. Furthermore, conventional NGS techniques cannot determine the 5' and 3' terminal sequences of the RNA viral genome. Therefore, the terminal sequences are determined one by one using rapid amplification of cDNA ends (RACE). However, since some RNA viruses have segmented genomes, the burden of the determination using RACE is proportional to the number of segments. To date, there is only a study attempting whole genome sequencing of multiple RNA viruses without using above mentioned methods, but the generated sequences' accuracy compared to the reference sequences was up to 97% and did not reach 100% due to the low read depth. Hence, we established novel methods, named PCR-NGS and RCA-NGS, that were optimized for an NGS machine, MinION. These methods do not require nucleic acid amplification with virus-specific PCR primers, physical viral particle enrichment, and RACE. These methods enable whole RNA viral genome sequencing by combining the following techniques: 1) removal of unwanted DNA and RNA other than the RNA viral genome by nuclease treatment; 2) the terminal of viral genome sequence determination by barcoded linkers ligation; 3) Amplification of the viral genomic cDNA using ligated linker sequences-specific PCR or an isothermal DNA amplification technique, such as rolling circle amplification (RCA). The established method was evaluated using isolated RNA viruses with single-stranded, double-stranded, positive-stranded, negative-stranded, non-segmented or multi-segmented genomes. As a result, all the viral genome sequences could be determined with 100% accuracy, and these mean read depths were greater than 2500×, at least using either of the methods. This method should allow for easy and economical determination of accurate RNA viral genomes.